Heteromolpadia joyceae, a new species of sea cucumber from New Zealand, with a key to New Zealand Molpadiidae (Echinodermata: Holothuroidea: Molpadiida) - Pawson, David L.; Vance, Doris J. (Zootaxa, 2007)
Heteromolpadia joyceae, new species, has been collected from depths of 258–632m off the east coast of New Zealand. It is distinctive in having a tough, leathery skin, gray with scattered red spots. Tables in body wall 100µm in diameter with three larger perforations; tail ossicles with 15–20 perforations, a three-pillared spire, and an average length of 300µm. A key to the eight species of Family Molpadiidae now known from the New Zealand region is provided.